POLA KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU PENGELOLAAN SARANA PRASARANA DAN LINGKUNGAN SEKOLAH - Samrin; Mulyadi, Edi; Hardian, Dafyar Eliadi (Perspektif : Jurnal Ilmu Administrasi, 2025)
This study aims to describe and analyze the leadership patterns of madrasah principals in improving teacher performance, managing facilities and infrastructure, and creating a conducive school environment at Madrasah Tsanawiyah (MTs) Khudrinnur, Kolaka Regency. The background of this study stems from the important strategic role of madrasah principals in supporting educational success, particularly in creating quality learning. Problems such as weak teacher motivation, irregular madrasah programs, and suboptimal utilization of school facilities and environments are the main focus of this study. The purpose of this study is to examine in depth how madrasah principals' leadership patterns are applied to foster teacher performance, effectively manage educational facilities and infrastructure, and create a school environment that supports the teaching and learning process. This study used a descriptive qualitative approach with a single case study conducted at MTs Khudrinnur. Data were collected through observation, in-depth interviews, and documentation, then analyzed thematically. The results indicate that madrasah principals implement participatory and supportive leadership patterns in developing teachers, namely through routine supervision, personal approaches, and motivation. In managing infrastructure, madrasah principals strive to optimize the effective use of existing facilities and involve teachers in the needs planning process. Meanwhile, in creating a conducive school environment, madrasah principals foster harmonious communication, prioritize family values, and create a safe and comfortable school atmosphere. This research contributes to strengthening Islamic educational leadership practices at the madrasah level, particularly in rural areas. It is hoped that these findings will serve as a reference for developing an effective and humanistic leadership model for madrasah principals. Keywords: Madrasah Principal Leadership, Teacher Performance, Infrastructure, School Environment.